Rational and optimal distribution of green infrastructure in urban areas - McGarity , Arthur; Dąbrowski , Wojciech (Instal, 2019)
Multiobjective optimization methods are being used to predict the most efficient allocation of financial sources in order to achieve the best trade-off solution that balances costs and the various benefits. These methods have been applied in several locations around the world. The approach developed by the U.S. EPA, called SUSTAIN, which uses heuristic evolutionary optimization, is briefly described here. Also, a simplified multiobjective approach, called StormWISE, which uses linear programming, has been applied to reduce combined sewer overflows (CSO) in Philadelphia. Both approaches are briefly described.
Keywords: green infrastructure; multiobjective optimization; CSO; bioretention